Exercise preconditioning alleviates photothrombotic ischemic stroke in mice by orchestrating neutrophils - Kim, Tae Yeon; Cho, Yun Seo; Park, Jae Yeon; Woo, Songwon; Yuk, Kihoon; Yi, Dong Heon; Jeong, In cheol; Jeon, Jin Pyeong; Bae, Yoe-Sik; Lee, Min-Chul; Moon, Hyo Youl (Frontiers in Physiology, 2025)
BackgroundIn ischemic stroke (IS) pathology, neutrophils are rapidly recruited to the infarcted brain and exacerbate tissue damage by releasing the amount of neutrophil extracellular traps (NETs). Previous studies have demonstrated that alleviating IS is associated with reduced accumulated neutrophils and NET levels. Notably, exercise preconditioning (EP) has the potential to modulate neutrophil function, thereby contributing to the amelioration of IS. This study compared the functional differences between resting and EP-induced neutrophils under IS pathology.MethodsEight-week-old C57BL/6J male mice underwent 8 weeks of voluntary exercise before photothrombotic ischemic stroke (PTI) surgery. Behavioral tests were conducted 2 days after PTI to verify the effects of EP on acute recovery following PTI. To evaluate whether EP affected neutrophil recruitment and chemotactic signaling, RT-qPCR was performed on infarcted cortical regions. A migration assay was performed to assess the migration capacity of blood-isolated neutrophils under IS. Plasma NET levels were quantified using enzyme-linked immunosorbent assay (ELISA), while NET presence in the brain was evaluated through immunofluorescence (IF) staining.ResultsExercise-preconditioned-PTI (EP-PTI) mice showed superior behavioral outcomes in grip strength and open-field tests both before and 2 days after PTI compared to sedentary-PTI (Sed-PTI) mice. EP also suppressed the expression of chemotactic signaling molecules following PTI, suggesting reduced inflammatory recruitment and infiltration. Furthermore, EP reduced the migration capacity of neutrophils and decreased NET formations in both plasma and brain 2 days after PTI surgery.ConclusionOur study demonstrates that EP enhances acute recovery in IS and may beneficially orchestrate IS pathology by inhibiting the migratory capacity and reducing NET formation in vivo.